INVESTIGATION OF THE MECHANISM OF RESISTANCE TO GLYPHOSATE HERBICIDE IN HAIRY FLEABANE - KASPARY,T.E. (2016)
ABSTRACT The resistance of weeds to herbicides is a consequence of one or more mechanisms in the plant, responsible for not allowing the herbicide to act properly at the active site. The objective of this study was to investigate the mechanism(s) of resistance to glyphosate in Conyza bonariensis. An experiment was conducted in November and December, 2012 and repeated in February and March, 2013 using a factorial arrangement of the treatments, where the factor A corresponded to biotypes of hairy fleabane, susceptible (S) and resistant (R); the factor B to seven rates of glyphosate from 0 to 11,520 g e.a. ha-1, and factor C were simulated environmental conditions of winter (12/8 oC day/night of temperature and 10/14 h of photoperiod) and summer (28/20 oC day/night of temperature and 14/10 h of photoperiod). An assay evaluating the shikimic acid was performed twice in the month of July 2013, with treatments arranged in a factorial arrangement, being factor A biotypes of hairy fleabane, S and R and the factor B seven glyphosate rates (0 to 28,8 mg a.e. L-1). The R biotype of C. bonariensis does not appear to present the sequestration of herbicide in the vacuole as the mechanism of resistance. However, the low accumulation of shikimate by the R biotype characterizes lower sensitivity of EPSPs enzyme to glyphosate, inferring that this is the present mechanism of resistance in plants of C. bonariensis. However, the resistance cannot be associated to a unique mechanism of resistance, requiring further studies to its understanding.